THE IMPROVEMENT OF STUDENTS SCIENTIFIC LITERACY THROUGH GUIDED INQUIRY LEARNING MODEL ON FLUID DYNAMICS TOPIC - Arifin, Lina; Sunarti, Titin (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2017)
This research was aimed to improve the students scientific literacy through guided inquiry learning model on Fluid Dynamics material. The type of research was pre-experimental design with one group pre-test and post-test design that used 1 experimental class and 2 replication classes. The data analyzed was the learnig implementation, scientific literacy aspects, and students responses. The result of this research shows that: (1) the implementation of guided inquiry learning model to improve students scientific literacy was done well and in accordance with the learning syntax; (2) there was an increase in the scientific literacy of high category in competency aspect that was in the competency to interpret data and scientific evidence. In addition, in the other aspects that were procedural knowledge aspect, local context aspect, and attitude of science interest aspect; and (3) the students responses showed very good category. The implementation of guided inquiry learning model can increase students scientific literacy level.